2021
DOI: 10.1111/are.15577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black mustard (Brassica nigra) seed oil on growth performance, digestive enzyme activities and immune responses in rainbow trout (Oncorhynchus mykiss)

Abstract: In the present study, effects of black mustard seed oil administration on growth performance, digestive enzyme activities and immune response in rainbow trout (Oncorhynchus mykiss) were evaluated. Rainbow trout were fed with three different doses of black mustard seed oil at the rate of 0.5% (BM0.5), 1% (BM1) and 2% (BM2) along with a control with no supplementation (0%) for 60 days. On 30th and 60th day of the study, digestive enzyme activities and immune responses were examined. At the end of the feeding tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In our study, LA increased on different sampling days in treatment groups. Some previous studies indicated that medicinal herbs and their bioactive compounds have positive effects on LA activity in rainbow trout (Salem et al, 2021;Lakwani et al, 2022). Haghighi et al (2014) reported that LA activity increased significantly in rainbow trout fry fed with 1%…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LA increased on different sampling days in treatment groups. Some previous studies indicated that medicinal herbs and their bioactive compounds have positive effects on LA activity in rainbow trout (Salem et al, 2021;Lakwani et al, 2022). Haghighi et al (2014) reported that LA activity increased significantly in rainbow trout fry fed with 1%…”
Section: Discussionmentioning
confidence: 99%
“…The decreased LPS activities in the LO groups may be due to high levels of saturated fatty acids (C18:0) in LO, which restrict lipid absorption [ 65 ]. Normally, TRY, a proteolytic enzyme, can present a close relationship between its higher protease activity and better growth performance in animals [ 66 ]. Therefore, higher TRY activities in the liver and intestines of the FO, SO and RO groups indicates better utilization of dietary amino acids, subsequently increasing the growth indexes of largemouth bass [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, in recent years, a great number of studies have intensively focused on application of organic-based feed additives that have stress relieving, anti-inflammatory, immunostimulant, antifungal, and antimicrobial properties (Asadi et al 2012;Balamurugan et al 2016;Hernandez et al 2016;Kirubakaran et al 2016;Mohamed et al 2018;Taştan & Salem 2021;Sönmez et al 2022). Among various organic-origin products, microorganisms, plants, plant extracts and essential oils have been tested in several recent studies as alternatives to drugs, chemicals and antibiotics (Bilen et al 2019(Bilen et al , 2020Arslan et al 2018;Sönmez et al 2015aSönmez et al , 2021Elbesthi et al 2020;Yilmaz et al 2019Yilmaz et al , 2020Amoush et al 2021;Lakwani et al 2021).…”
Section: Introductionmentioning
confidence: 99%